Manajemen Lalu Lintas Guna Mengatasi Kemacetan Lalu Lintas Simpang Jalan Z.A. Sugianto – Jalan Masjid Al Alam Kota Kendari - Ridwan Syah Nuhun; Nasrul Nasrul; Yasir Saleh Arafah (Jurusan Teknik Sipil, Universitas Halu Oleo, 2024)
Traffic management aims to regulate vehicle flow to optimize infrastructure usage and facilitate smoother movement. This study proposes solutions to address congestion during peak hours at the intersection of Jalan Z.A. Sugianto and Jalan Masjid Al Alam while improving road performance. Data was collected through field surveys and analyzed using the PKJI 2023 method. The findings indicate that the traffic volume during peak hours (5:00–6:00 PM local time) reached 2,632 PCU/hour, exceeding the intersection's capacity of 2,472 PCU/hour, resulting in a degree of saturation of 1.06, which corresponds to a Level F service. Implemented strategies include one-way traffic management on Jalan Masjid Al Alam and road widening on major routes.